You need to notice that if you add the equations, the variable y will be eliminated, hence, performing the addition of equations, yields:

`2x + y + x - y = 15 + 45`

Reducing duplicate terms yields:

`3x = 60 => x = 60/3 => x = 20`

Substituting 20 for x in the equation `x - y = 45` yields:

`20 - y = 45 => -y = 45 - 20 => -y = 25 => y = -25`

**Hence, evaluating the solution to the system, using elimination method, yields **`x = 20, y = -25.`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.